Correlation Between Socio Economic Characteristic And Entrepreneur’s Motivation of Dairy Goat Farmers With Dairy Goat Business Sustainability - Nurlina, Lilis; Arief, Hasni; Yunasaf, Unang; Sulistyati, Marina; Alim, Syahirul; Mauludin, M. Ali (Jurnal Ilmu Ternak Universitas Padjadjaran, 2024)
ABSTRACTThe aim of this research were to study : (1) socio economic characteristic of dairy goat farmers; (2) entrepreneur’s motivation of dairy goat farmers; (3) dairy goat sustainability business; (4) dairy goat farmer’s strategy to business sustainability; ( (5) correlation between socio economic characteristic and entrepreuneur motivation farmer with dairy goat business sustainability. The research used mix method, there were quantitative and qualitative approach. Respondents of this research were 15 dairy goat farmers, that are variants from small scale business, medium and big scale.  The result of this research showed that : (1) characteristic socio economic of dairy goat farmers has been supported to business sustainability especially from education, age, farming experiences and production facilities; (2) entrepreneur’s motivation was medium category, because dairy goat farmer has business logic it means if it is no longer profitable then switch to mixed business (3) dairy goat sustainability business was medium category the level of business sustainability is not optimal (medium category), because this business has a risk of difficulty in marketing its milk products; (4) the farmers strategy in maintaining this business are : making promotion and increase resellers  in order to increase consumers; (5) there were positive correlation between socio economic with sustainability business (rS  = 0.542) and between entrepreneur motivation with dairy goat sustainability business (rS = 0.572 )